Paradigma Pemberdayaan Ekonomi Rakyat: Keterpaduan Sektor Formal dan Informal - Edy Suandi Hamid (Universitas Islam Indonesia, 2006)
The people economy is often called the economic life of people, this terminology contains specific meaning. The economy of people describes the actor of economy, but the economic life of people explains the economical system. The Indonesian people economy play important role, for Indonesian economy, and also it is motivated and supported by Indonesia govemment. For that reason, the strict policy for economy is needed in ordereconomy unit can develop in particular to increase Indonesian national output, finally, the Indonesian economy building towards to a just, prosperous, welfare, and independent society.